Technological change and risk management : banking institutions in the 21st century - Subero, Jessel ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Examines the possible effects that electronic banking systems may have on banking institutions from a risk management viewpoint. Highlights some salient issues that confront regulators in this new dynamic.